OPTIMIZATION OF ROUTES FOR DISTRIBUTION OF THE INGREDIENTS OF THE SCHOOL MEALS IN SCHOOLS OF THE CITY OF BARRETOS – SP - Tová, Augusto César; Mendes, Oswaldo Lazaro (Revista Interface Tecnológica, 2020)
This article aims to find the shortest route for the delivery of lunch ingredients to 46 schools in the city of Barretos - SP, since one of the objectives of logistics in terms of transport, aims to seek the shortest possible route to deliver with agility and lower cost. For the execution of this article, descriptive, exploratory and quantitative research was used and to understand the proposed problem, Google Maps was used to capture the distances, with schools and two entrances to the city. This work was developed simulating the use of a truck and with two trucks due to the weather. In order to find a shorter route to be covered, the work used the Evolutionary Method, from Solver, which is a method capable of solving problems based on evolutionary algorithms. As a result, in all cases, the reduction was significant in terms of the distances covered, generating gains in fuel economy and time. With this study it is concluded that the use of technologies is of utmost importance in order to reduce and optimize delivery routes, and the Excel Solver tool is very effective in this regard.